Identifying an Optimal Screen Mesh to Enable Augmentorium-Based Enhanced Biological Control of the Olive Fruit Fly Bactrocera oleae (Diptera: Tephritidae) and the Mediterranean Fruit Fly Ceratitis capitata (Diptera: Tephritidae). Issue 3 (28th May 2022) - Desurmont, G A; Tannières, M; Roche, M; Blanchet, A; Manoukis, N C
Abstract: The augmentorium is a cost-effective screened enclosure designed to receive fruits infested with insect pests, retain the pests inside but let their natural enemies escape to enhance biological control of pest populations. Screen selection is critical to ensure that an augmentorium is effective for a particular system. Here we tested five types of screens with a mini-augmentorium design and measured the escape of four insect species under laboratory conditions: the pests olive fruit fly Bactocera oleae (Rossi) (Diptera: Tephritidae) and Mediterranean fruit fly Ceratitis capitata (Wiedemann) (Diptera: Tephritidae), and the parasitoids Psyttalia lounsburyi (Silvestri) (Hymenoptera: Braconidae) and Psyttalia ponerophaga (Silvestri) (Hymenoptera: Braconidae). The sex ratio of insects that escaped the screens was compared to the sex ratio of insects that could not escape. Results showed that one screen type ('crystal mesh') was the best for the purpose of designing a functional augmentorium: it retained 90% of B. oleae adults and 100% of C. capitata adults while letting 72% of Psyttalia lounsburyi adults and 94% of P. ponerophaga adults escape. The other screen types tested were suboptimal, either because they let too many flies freely escape or because they retained too many parasitoids. Sex ratio was almost always similar for insects that managed to escape the screens and insects that were retained, except for P. ponerophaga and the screen type 'light mesh'. These results are promising for the development of a functional augmentorium against the olive fruit fly and further implementation against Mediterranean fruit fly.